The Prostaglandin E2 Pathway and Breast Cancer Stem Cells: Evidence of Increased Signaling and Potential Targeting - Walker, Olivia L.; Dahn, Margaret L.; Power Coombs, Melanie R.; Marcato, Paola (Frontiers in Oncology, 2022)
Culprits of cancer development, metastasis, and drug resistance, cancer stem cells (CSCs) are characterized by specific markers, active developmental signaling pathways, metabolic plasticity, increased motility, invasiveness, and epithelial-mesenchymal transition. In breast cancer, these cells are often more prominent in aggressive disease, are amplified in drug-resistant tumors, and contribute to recurrence. For breast cancer, two distinct CSC populations exist and are typically defined by CD44+/CD24- cell surface marker expression or increased aldehyde dehydrogenase (ALDH) activity. These CSC populations share many of the same properties but also exhibit signaling pathways that are more active in CD44+/CD24- or ALDH+ populations. Understanding these CSC populations and their shared or specific signaling pathways may lead to the development of novel therapeutic strategies that will improve breast cancer patient outcomes. Herein, we review the current evidence and assess published patient tumor datasets of sorted breast CSC populations for evidence of heightened prostaglandin E¬2 (PGE2) signaling and activity in these breast CSC populations. PGE2 is a biologically active lipid mediator and, in cancer PGE2 promotes tumor progression and poor patient prognosis. Overall, the data suggests that PGE2 signaling is important in propagating breast CSCs by enhancing inherent tumor-initiating capacities. Development of anti-PGE¬2 signaling therapeutics may be beneficial in inhibiting tumor growth and limiting breast CSC populations.